Development of Hybrid Discovery Learning (HDL) Model for Integrated Social Studies Learning - Nadjamuddin, Lukman; Amus, Sunarto; Jamaludin, Jamaludin; Usman, Sriati; Rore, Idrus A.; Tadeko, Nurgan; Zaky, Muhammad (Technium Social Sciences Journal, 2022)
The Covid-19 crisis has led to a widening of the scope and role of online-based learning and information technology (IT)-based education. It is believed that the IT based education will play significant roles even when the Covid crisis ended. Online based learning requires good preparation and contextual schemes to achieve learning outcomes. Students will benefit the online based teaching once it is well prepared and equipped with interactive IT. A combination off- and online learning, known as hybrid learning, when merged to discovery learning will enhance more student interaction. It can measure the interaction numerically and laterally of students. Also, students will explore real-world problems through reality learning condition. This study was developed using the ADDIE model and qualitative descriptive approach. The objective was to evaluate whether using hybrid in the discovery learning will bring barriers for teacher and whether it is effective to achieve students learning outcomes. In this study, the hybrid and discovery learning were combined onto Hybrid Discovery Learning (HDL) model. The developed model was tested with two different focus group discussions (FGD), followed by 24 teachers and instructors of the social studies, and tested for 12 classes. The results demonstrate that the HDL model is successfully support the integrated learning of social studies. However, the benefits of implementing HDL model can only be optimal when several aspects (26 aspects according to the results of the second FGD) such as powering digital means, develop good IT based teaching materials, preparation of templates, and adjust suitable evaluation system, are well done.